The science-policy interface of ecological governance: functions, risks, and practices of boundary objects in China - Wang, Qinhua; Wang, Penglong; Xu, Bingxin; Wang, Bao (Frontiers in Environmental Science, 2026)
Effective interactions between science and policy are essential for sustainable development in ecological governance. Boundary objects connect heterogeneous communities and facilitate knowledge integration, providing a unique perspective for understanding the science-policy interface (SPI). However, a systematic understanding of their functions, mechanisms, and dual-sided effects is lacking. This paper constructs an integrated “function-mechanism-effect” analytical framework to systematically examine boundary objects. It explores their theoretical connotations and multidimensional functions in SPI, examines their action mechanisms, and dialectically assesses their positive effects as “glue” and potential risks as “blindfolds.” The paper analyzes typical boundary objects in China’s ecological governance, including the “ecological protection red line,” the “mountains, waters, forests, lakes, grasses, and sands” system, and the “two mountains theory,” while also exploring emerging tools like GEP accounting. Through a comparative analysis, the study reveals how these cases form a complementary “governance tools matrix,” demonstrating their complex operations and inherent risks. The findings refine boundary object theory and offer practical guidance for the prudent design and “life-cycle management” of these tools, aiming to foster more inclusive and adaptive governance models.